Weld Formation and Characteristics of Hot-Wire Laser Welding in Aluminum Alloy Narrow-Gap Joints - Jukkapun Greebmalai; Shun Sadasue; Keita Marumoto; Eakkachai Warinsiriruk; Motomichi Yamamoto (Metals, 2025)
This study joins a 20 mm thick 5000-series aluminum alloy using hot-wire insertion combined with narrow-gap laser welding to evaluate the feasibility and welding characteristics of this technique. The findings indicate that weld formation is primarily influenced by the laser energy density and material deposition rate. A strategy for improving weld beads is introduced incorporating a reoriented laser spot during the final pass on narrow-gap joints. This approach improves penetration and produces defect-free joints. The optimal processing conditions result in complete joint formation with four welding passes. Microstructural analysis reveals that the aluminum matrix morphology evolves according to the local thermal history during welding. Measurements show that the weld region is slightly harder than the base metal, whereas slightly lower hardness is observed at the fusion line and inter-pass boundaries, which correlates with the microstructure result.